Ewe mastitis and milk safety - Mendonça, Álvaro (2013)
In order to assess the safety of milk used for produce raw milk ewe cheeses, we collect 60 milk aseptic samples from 60 half udders, during nine weeks, totalizing 540 samples. As result we identified 19 different microorganisms in 86 glands during the sampling time. Only one microorganism (S. aureus) could be dangerous for human health, found in the 6th week. All the others were almost all pathogens for animal itself. We considered as infected those half udders presenting more than two positive isolations during the all period of sampling. From the total glands, 38,3% was negative, 48,7% with two or fewer infections and 15% were consistently infected. We found two females with a double mastitis, two females with a single mastitis with a persistent infection and three females with single mastitis but with less than 4 isolations. Two animals represented 50% of the total infected half udders and 26,7% of the total isolations, showing the importance of individual mastitis control in ewes.